Presepsi Masyarakat terhadap Jalur Pedestrian Pada Ruas Jalan Veteran Lamongan - Sophie Priyanka Ardhaneswari; Hammam Rofiqi Agustapraja (Jurnal Talenta Sipil, 2023)
As the population increases, the speed of population movement also increases and the availability of proper infrastructure in crowded centers decreases. One of the problems in terms of pedestrian facilities in Indonesia's urban areas is the lack of fulfillment of pedestrian needs, both in terms of quality and quantity. The development of pedestrian facilities in Indonesia has not become a priority comparable to the development of facilities for other modes of transportation. The lack of public understanding of pedestrian path facilities indicates the need for attention from the government in fulfilling the functional needs of pedestrian paths. Because of that it is important to understand the public's perception of the need for pedestrian facilities on Jalan Veteran Lamongan. Distribute questionnaires to the community and then carry out validity and reliability tests so as to produce public perceptions of pedestrian lane facilities on veteran roads, namely pedestrian paths, which need additional attention for facilities and infrastructure. 34% of respondents said there were many deficiencies in the quality of the sidewalks, then 31% said they lacked the quality of facilities for the disabled, then 33% of respondents said they lacked the quality of accessibility, then 31% of respondents felt they lacked the level of completeness of facilities, then 33% respondents said they lacked the level of safety, then as many as 36% of respondents felt they lacked the level of security, and finally 37% of respondents felt they lacked the level of satisfaction.